New constraints on a complex relation between globular cluster colors and environment - Powalka, Mathieu; Schönebeck, Frederik; Grebel, Eva K. (Arxiv, 2016)
We present an analysis of high-quality photometry for globular clusters (GCs) in the Virgo cluster core region, based on data from the Next Generation Virgo Cluster Survey (NGVS) pilot field, and in the Milky Way (MW) based on VLT/X-Shooter spectrophotometry. We find significant discrepancies in color-color diagrams between sub-samples from different environments, confirming that the environment has a strong influence on the integrated colors of GCs. GC color distributions along a single color are not sufficient to capture the differences we observe in color-color space. While the average photometric colors become bluer with increasing radial distance to the cD galaxy M87, we also find a relation between the environment and the slope and intercept of the color-color relations. A denser environment seems to produce a larger dynamic range in certain color indices. We argue that these results are not due solely to differential extinction, IMF variations, calibration uncertainties, or overall age/metallicity variations. We therefore suggest that the relation between the environment and GC colors is, at least in part, due to chemical abundance variations, which affect stellar spectra and stellar evolution tracks. Our results demonstrate that stellar population diagnostics derived from model predictions which are calibrated on one particular sample of GCs may not be appropriate for all extragalactic GCs. These results advocate a more complex model of the assembly history of GC systems in massive galaxies that goes beyond the simple bimodality found in previous decades.